" Artificial Intelligence in E-Governance in India: Exploring the potential applications, benefits, and ethical implications of integrating AI technologies in electronic governance systems to enhance service delivery and efficiency in India. " (International Journal of Food and Nutritional Sciences, 2023)
Artificial Intelligence (AI) is revolutionizing the landscape of electronic governance (E-Governance) in India. This research explores the impact, challenges, and opportunities of AI in the realm of e-governance, shedding light on its potential to enhance administrative efficiency, transparency, public service delivery and accessibility in public administration. This research delves into the dynamic synergy between Artificial Intelligence and electronic governance in India. It comprehensively explores the multifaceted applications and advantages offered by the integration of AI technologies in the public sector. Beyond its transformative potential, this research also engages with the ethical considerations, unveiling a nuanced discussion of the impact of AI adoption on service delivery and administrative efficiency in the Indian e-governance landscape. From optimizing public services to addressing ethical concerns, this paper presents a holistic view of the evolving landscape of e-governance in India, propelled by the power of AI. It explores the wide-ranging applications, benefits, and ethical implications of integrating AI technologies into governmental processes. Through a comprehensive analysis, it unveils the profound impact of AI on enhancing service delivery, reflecting the nation's pursuit of innovation.